AN INVESTIGATION ON THE EFFECT OF GLASS FIBER CONTENTS TO THE TOP LOAD IN THE CONCRETE PIPES - Yildiz, Servet; Ulucan, Zuelfue Cinar (Gazi Univ, Fac Engineering Architecture, 2008)
In this study, the variation of top load strength of the concrete pipes containing %0.2, 0.4 and %0.6 fiber-glass (by weight) has been investigated. The concrete pipes have been tested according to the standard procedures (TS 821 EN 1916). From these tests, it is observed that the fracture load of the concrete pipes containing fiberglass is more than that of the concrete pipes without containing fiber-glass. The top loads of the concrete pipes have increased when the fiber-glass rate is increased. In addition, the top pressure load of the concrete pipes obtained under the same conditions was investigated after the pipes in which flew the sewage and rain water were waited under the soil during one year. According to the obtained results, it is seen that after twenty eight days the top load strength concrete pipes containing %0.6 fiber-glass has been increased %21.54 and after one year the top load strength of the concrete pipes containing the same fiber-glass has been increased %27.40. The load-displacement curves have been drawn depending on the test results. It is also seen that the displacement and the fracture load of the concrete pipes have been increased.
Keywords: Top load; fiber glass; concrete pipe